Earthquake prediction and monitoring using unusual animal behavior - Aibinu, Abiodun Musa; Astuti, Winda; Salami, Momoh Jimoh Emiyoka; Akmeliawati, Rini; Abdul Muthalif, Asan Gani (IIUM Press, 2011)
Earthquake is one of the most destructive natural disasters that killed many people and destroy lots of properties. The ability to predict the earthquake can lead to great reduction in catastrophic effect caused by this unwanted phenomenon. Earthquake predictions involve the study of the phenomenon prior to the earthquake. As many observation of the earthquake prior phenomenon, unusual animal behavior is one of the precursor phenomena prior to the earthquake. Among the geophysical stimuli which lead as precursor signals for earthquake, the changes of electric field and electromagnetic can be detected by animals and has been attributed to the reason for unusual animals behavior. On the other hand, changes in magnetic field reported before earthquakes are less than one ten thousandth of the earth magnetic field, thus it is highly impossible for this to be the cause of unusual animal behavior. Unusual animal behavior prior to the earthquake would be cause by pulsed electric field rather than magnetic fields. The observation to the experiment result shown that the aquatic animal are more sensitive to the changing of electric field compare to the land animals, since it has high sensitivity in receiving changing of electric fields. Earthquake is a movement or displacement of the earth’s surface, resulting in release of energy through a sudden dislocation in the segment of the earth crush [6]. The necessity associated with this earthquake needs not be over emphasized. As earthquake is one of the most destructive natural disasters that killed many people and destroy many things. The very big tsunami triggered by a magnitude 9 in Richter scale of northern Sumatra Island on December 26, 2005 rolled through the Indian Ocean, and killed more than 150,000 people (Wikipedia,2011). Similarly, The recent giant earthquake magnitude 9 R that followed by the tsunami on March 11, 2011, happened in Tohoku, Japan [5] and killed 18.000 people. Moreover the ability to know the occurrence of earthquake ahead of time can lead to reduction in causality and damage caused by this unwanted phenomenon.